(untitled) (Journal of Ideas in Health, 2021)
Background: Although we are in the era of the 21st-century, some people’s lifestyles are still unchanged. People are still eating crude or undercooked fish, which puts them at risk for opisthorchiasis infection. This study aimed to measure knowledge and prevention behavior regarding opisthorchiasis among people resident in Ubon Ratchathani, the northeastern region of Thailand. Methods: A cross-sectional study was conducted from 2nd October 2018 to 26th December 2018. The data was collected via a self-administered household survey using a systematic random sampling technique. Univariate and bivariate analyses such as the chi-square test were performed. SPSS version 16 was used to analyze the data, and the significance of less than 0.05 was considered. Results: Four hundred and fifteen households have completed the questionnaire. Most of the participants were female (50.1%), aged 15-59 years old (75.3%), married (64.8%), had completed elementary school (46.3%), worked in agriculture (31.6%), and had a monthly salary of on average of 6,525 baht. Most of the respondents reported excellent behavior (94.2%) and good knowledge (80.5%) to prevent opisthorchiasis, respectively. However, there was no significant association between participants’ characteristics and the related behavior to prevent opisthorchiasis (p>0.05). Conclusion: Despite efforts to educate the community, some people lack preventive knowledge and exhibit behavior associated with a higher risk of opisthorchiasis.